Physico-chemical properties of high and low amylose rice flour - Kemashalini, K.; Prasantha, B.D.R.; Chandrasiri, K.A.K.L. (University of Jaffna, 2018)
Physico-chemical and pasting properties of high-amylose rice flour (Bg 360) and low-amylose rice flour (At 405) were tested in this study. A modified visco-amylograph method was used to test the pasting behavior of rice flours. Amylose content, damaged starch, swelling power, water absorption capacity and sedimentation volume showed a significant difference between the two rice flours. The At 405 rice flour contained significantly higher damage starch content (%), swelling power (g/g), water absorption capacity (%) and low crude fat content (%) compare to Bg 360. The amylose content of rice flour showed a strong but negative correlation with damaged starch, swelling power and water absorption capacity of rice flour. Damaged starch showed a significant positive correlation with swelling power and water absorption capacity. Despite the breakdown of the viscosity (mPa s) did not show significant differences, setback viscosity, pasting temperature and time of high-amylose flour showed significantly higher values than low-amylose flour.
Keywords: Amylose; Physico-chemical; Rice flour; Viscosity; Crude fat; Crude protein